2010
DOI: 10.3109/00016480903062160
|View full text |Cite
|
Sign up to set email alerts
|

Indication for elective neck dissection for N0 carcinoma of the parotid gland: a single institution's 20-year experience

Abstract: Lymph node metastasis was detected in 27 of 71 patients who underwent neck dissection. Node metastasis was detected in 19 (61.3%) of 31 patients in whom high-grade malignancy was suggested and in 8 (22.9%) of 35 patients in whom intermediate-grade malignancy was suggested preoperatively. There was no metastasis in any of the five patients in whom low-grade malignancy was suggested. Occult metastasis was noted in 8 of 51 patients. The rate at which the histological grade was accurately diagnosed before surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 20 publications
4
60
2
2
Order By: Relevance
“…As pointed out in the literature, regional metastases are most common in SCC, AC NOS, MEC, CXPA, SDC, UCa and less common in AcCC and AdCC [24, 10, 11, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in the literature, regional metastases are most common in SCC, AC NOS, MEC, CXPA, SDC, UCa and less common in AcCC and AdCC [24, 10, 11, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that it should be performed in all cases of PPC, regardless of its stage and type [3, 11, 16]. Other authors recommend it only in local T3/T4 and/or high grade tumour and/or tumours of high risk histology [7, 10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Без со-мнения, метастатическое поражение регионар-ных лимфоузлов, выявляемое в 25-38% случаев, крайне негативно влияет на выживаемость боль-ных раком ОСЖ [5]. Некоторые авторы рекомен-дуют проводить профилактическую шейную лимфодиссекцию даже при N0, аргументируя это тем, что у 15,8-22% таких пациентов выявля-ются лимфогенные метастазы [3,10,16]. Обычно метастазами поражаются лимфоузлы, распо-ложенные внутри ОСЖ или в непосредствен-ной близости от нее, реже -верхние и средние шейные, а также подчелюстные лимфоузлы [17].…”
Section: обсуждение и заключениеunclassified
“…High tumor grade, extraparotid extension, a tumor size of ≥4 cm and facial nerve involvement are associated with nodal disease (4). Even if the option of selective neck dissection is determined on the basis of histological grade or primary tumor stage (T stage), an accurate pre-operative assessment of the histological grade may be difficult in patients with parotid carcinoma (5,6). In previous studies, it has been reported that more than half of T4-staged parotid carcinoma patients exhibit neck node metastasis (6).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the option of selective neck dissection is determined on the basis of histological grade or primary tumor stage (T stage), an accurate pre-operative assessment of the histological grade may be difficult in patients with parotid carcinoma (5,6). In previous studies, it has been reported that more than half of T4-staged parotid carcinoma patients exhibit neck node metastasis (6). As a result, we recommend surgery with elective neck dissection (END) for T4-staged parotid carcinoma.…”
Section: Introductionmentioning
confidence: 99%